FACTORS INFLUENCING FINANCIAL DISTRESS IN REGENCY/CITY GOVERNMENTS IN SOUTH SUMATRA PROVINCE - Azzura, Meisya; Dewata, Evada; Frymaruwah, Edwin (Jurnal Aplikasi Akuntansi, 2025)
This research is principally intended to assess the impact of the Budgetary Solvency Ratio, Efficiency Ratio, and Growth Ratio on financial distress in district/city governments in South Sumatra Province. This analysis is motivated by the urgency of regional financial conditions to support the sustainability of public service delivery. A quantitative method is employed in this study, utilizing secondary data derived from regional government financial reports for 2019–2023. The study population included 17 district and city governments in South Sumatra Province, selected using a non-probability sampling technique. The methods of data analysis employed include descriptive statistical analysis, classical assumption testing (normality, multicollinearity, autocorrelation, and heteroscedasticity tests), and panel data regression analysis. The findings of this research reveal that the budgetary solvency ratio negatively and significantly influences financial distress; the efficiency ratio does not have a significant effect, while the growth ratio has a positive and significant impact on financial distress. A simultaneous analysis reveals that all three independent variables contribute meaningfully to variations in financial distress among local governments. This study contributes both theoretically and practically to the understanding of financial distress in local governments. Theoretically, it refines the application of financial distress theory by showing that the budgetary solvency ratio plays a more decisive role than efficiency and growth ratios in determining financial distress.  Practically, the findings provide valuable insights for policymakers and local government leaders by highlighting the need to prioritize financial solvency, strengthen revenue growth capacity, and adopt balanced expenditure management.